(untitled) (SciELO Preprints, 2021)
This papper seeks to think about the bases of a possible criticism undertaken by Michel Foucault around neoliberalism and its relationship with education. Based on a bibliographic survey that covers the works developed by Foucault from a political history of governmentality, we will try to demonstrate how neoliberalism, in Foucault’s eyes, should be understood as a way of life and as a government practice responsible for the production of modes of subjectivation identified with self-entrepreneurship as the aesthetics of neoliberal existence. At first, we go through the contours of Foucault’s thinking around a genealogy of the arts of government and of the processes of subjectification. The second moment is dedicated to trying to understand the effects by which neoliberalism is constituted as an ethos responsible for producing an experience of a capitalized and financialized education. Finally, our final considerations are dedicated to the elaboration of a critique around the neoliberal governmentality regime based on the contributions made by Michel Foucault.